Chapter 3 - Cacao - Mayorga Gross, Ana Lucía (2023)
Cocoa and cocoa derivatives are recognized for having a rich and complex nature. This is highly dependent on the cocoa genetics, on the terroir where cocoa is produced and processed, on the different transformation steps and on the final formulation of the product. Fats and proteins can constitute the highest percentage of different cocoa products, in addition a great variety of phytochemicals can be found, as for example, polyphenols as flavonoids, methylxanthines, fatty acids, phenolic acids, vitamins, minerals, peptides, N-phenylpropenoyl-l-amino acids, biogenic amines, among others. After intake, the bioavailability, absorption, metabolism, and excretion of these phytochemicals are mainly influenced by several factors as nature and dose of the phytochemicals, food matrix and interactions with other metabolites, subject profile and its overall health status and interactions with the microbiota. During these processes, a series of transformations lead to the production of metabolites which might exert biological activity with different implications. Increasing evidence shows that cocoa and derivatives intake has a potential role in health promotion suggesting acute positive effects over vascular parameters and cardiovascular performance, especially when containing significant amounts of flavonoids. Nonetheless, the relation between cocoa intake and health must be done with integrative approaches. This chapter aims to review the cocoa and cocoa derivatives composition, and its change during postharvest and processing steps. Furthermore, the relation between composition and metabolites reported in plasma and urine after intake of cocoa and cocoa products is shown. A review of some of the physiological mechanisms associated with the presence of metabolic products is addressed, with special focus on cardiovascular performance. Finally, evidence is presented regarding clinical interventions with cocoa and cocoa products, emphasizing cardiovascular health.